Pengaruh Keterampilan Kerja dan Disiplin Kerja terhadap Produktivitas Kerja Karyawan pada PT Subur Makmur Lintang Gemilang Kota Tangerang - Elizabeth Tambunan; Suryanto Sosrowidigdo; Siti Nurjanah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
Employee productivity is a crucial element for corporate success amidst increasingly intense business competition; however, at a distribution and trading company in Tangerang City, productivity has not reached optimal levels due to uneven work skills and discipline. This study aims to examine the impact of work skills and work discipline on employee productivity, both individually and simultaneously. The study employs an associative quantitative approach using a saturated sampling technique involving 50 employees from the operations and production divisions. Data were collected via questionnaires and analyzed using multiple linear regression with statistical software. The results indicate that work skills have a positive and significant impact on employee productivity, and work discipline also demonstrates a positive and significant influence—contributing relatively more than work skills. Furthermore, both variables simultaneously exert a significant influence on productivity, with a high level of contribution. Other components are influenced by external factors beyond the scope of the research model. These findings confirm that enhancing employee productivity requires a comprehensive strategy involving continuous skills development and the implementation of consistent, objective, and fair work discipline within the company.